LESSON PLANS FOR TEXT COMPREHENSION AND INTERPRETATION - da Silva, Rosiane Pereira (Seven Editora, 2026)
This chapter presents several lesson plans focused on the comprehension and interpretation of texts in Portuguese language teaching, using different textual genres such as short stories, poems, chronicles, fables, narratives, informative texts, and advertisements. The proposed activities aim to develop critical reading, textual analysis, meaning-making, and reflection among students on social, cultural, and emotional themes present in the texts studied. The lesson plans emphasize pedagogical strategies that encourage active student participation, such as hypothesis generation based on titles, collective reading, debates, oral and written interpretation, vocabulary analysis, text production, and group discussions. These methodologies favor the construction of knowledge in a dynamic and meaningful way. The selected texts address varied themes, including consumption, childhood, imagination, advertising, social inequality, recycling, human behavior, feelings, identity, prejudice, family relationships, and social values. Thus, the chapter demonstrates the importance of reading as an instrument for critical, civic, and reflective education. Beyond textual interpretation, the lesson plans encourage the development of creativity and written production, proposing activities in which students write texts, reflect on personal experiences, and express opinions. Assessments are conducted continuously through participation, problem-solving exercises, debates, and written production. This chapter highlights that pedagogical planning combined with the use of different text genres contributes to making the teaching of Portuguese more attractive, participatory, and efficient, promoting the development of students' reading, interpretation, and argumentation skills.